2012
DOI: 10.1590/s1413-35552012005000057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of proprioceptive exercises in the treatment of rotator cuff disorders in nursing professionals: a randomized controlled clinical trial

Abstract: Background: Shoulder pain in nursing professionals may lead to limitations in occupational and daily activities and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(59 citation statements)
references
References 44 publications
(63 reference statements)
1
57
0
1
Order By: Relevance
“…Home exercise programme with 1 or 2 sessions with a physiotherapist per week for the first month followed by additional treatment over the next 4 weeks to a maximum of 12 sessions Individualized exercise programme comprised of stretching and strengthening to regain normal dynamic stability studies (Walther et al, 2004;Giombini et al, 2006;Calis et al, 2011) reported the Constant score, two studies (Baskurt et al, 2011;Martins and Marziale, 2012) reported the Western Ontario Rotator Cuff index, two studies (Ludewig and Borstad, 2003;Østerås et al, 2009 reported the Shoulder Rating Questionnaire, and one study (Lombardi et al, 2008) reported the Disabilities of the Arm, Shoulder and Hand questionnaire (Table 4).…”
Section: Outcome Measures and Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Home exercise programme with 1 or 2 sessions with a physiotherapist per week for the first month followed by additional treatment over the next 4 weeks to a maximum of 12 sessions Individualized exercise programme comprised of stretching and strengthening to regain normal dynamic stability studies (Walther et al, 2004;Giombini et al, 2006;Calis et al, 2011) reported the Constant score, two studies (Baskurt et al, 2011;Martins and Marziale, 2012) reported the Western Ontario Rotator Cuff index, two studies (Ludewig and Borstad, 2003;Østerås et al, 2009 reported the Shoulder Rating Questionnaire, and one study (Lombardi et al, 2008) reported the Disabilities of the Arm, Shoulder and Hand questionnaire (Table 4).…”
Section: Outcome Measures and Outcomesmentioning
confidence: 99%
“…Nine studies were conducted in Europe (Walther et al, 2004;Giombini et al, 2006;Engebretsen et al, 2009Engebretsen et al, , 2011Østerås et al, 2009Baskurt et al, 2011;Calis et al, 2011;Kromer et al, 2013;Littlewood et al, 2014a), two studies were conducted in North America (Ludewig and Borstad, 2003;Kachingwe et al, 2008), two in South America (Lombardi et al, 2008;Martins and Marziale, 2012), and one study was conducted in Australia (Yiasemides et al, 2011). An association between geographical location and clinical outcome is not clearly supported by this data.…”
Section: Contextual Factorsmentioning
confidence: 99%
See 3 more Smart Citations